Oversharing: Urgensi Privasi di Era Digital - Alpiah, Siti; Asbari, Masduki; Saputri, Indah Ayu; Adilya, Nur Rahma (AGUSPATI RESEARCH INSTITUTA, 2024)
The purpose of this study is to find out the causes of oversharing by viralizing privacy details to get attention. This study report uses a descriptive qualitative method by doing simak catat because the source of data obtained by listening to oral narratives from the Youtube channel Satu Persen - Indonesian Life School entitled